Peran Guru dalam Mendiagnosis Kesulitan Literasi Numerasi di Sekolah Dasar Negeri Pondok 01 - Salsabila Adwitiya Sarwahita; Tri Sutrisno; Meidawati Suswandari (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The role of teachers is important in managing students' educational process at school. The results of observations and interviews at SD Negeri Pondok 01 showed that numeracy literacy was still relatively low. These results were obtained from student data regarding student report cards, exam scores, and daily assignment scores which were still below the kkm. In interviews with teachers, students who experienced numeracy literacy difficulties were in grades 2, 4, 5, and 6 with a total of 7 students. The research method used is a qualitative research method, the samples in this study were taken from students and class teachers at Pondok 01 State Elementary School. This research discusses the role of teachers in diagnosing numeracy literacy difficulties. Difficulties experienced by students in the material on subtraction arithmetic operations, multiplication and decimal number arithmetic operations, porogapit division, and volume on flat shapes. In this problem, the teacher's role is very important in overcoming the problems experienced by their students, therefore there are 4 steps to overcome this problem, namely identification, diagnosis, prognosis, and providing assistance or therapy.